Chloroquine Eliminates Cancer Stem Cells Through Deregulation of Jak2 and DNMT1. (18th August 2014) - Choi, Dong Soon; Blanco, Elvin; Kim, Yoo-Shin; Rodriguez, Angel A.; Zhao, Hong; Huang, Tim Hui-Ming; Chen, Chun-Liang; Jin, Guangxu; Landis, Melissa D.; Burey, Lacey A.; Qian, Wei; Granados, Sergio M.; et al.
Abstract : Triple negative breast cancer (TNBC) is known to contain a high percentage of CD44 + /CD24 −/low cancer stem cells (CSCs), corresponding with a poor prognosis despite systemic chemotherapy. Chloroquine (CQ), an antimalarial drug, is a lysotropic reagent which inhibits autophagy. CQ was identified as a potential CSC inhibitor through in silico gene expression signature analysis of the CD44 + /CD24 −/low CSC population. Autophagy plays a critical role in adaptation to stress conditions in cancer cells, and is related with drug resistance and CSC maintenance. Thus, the objectives of this study were to examine the potential enhanced efficacy arising from addition of CQ to standard chemotherapy (paclitaxel) in TNBC and to identify the mechanism by which CQ eliminates CSCs in TNBCs. Herein, we report that CQ sensitizes TNBC cells to paclitaxel through inhibition of autophagy and reduces the CD44 + /CD24 −/low CSC population in both preclinical and clinical settings. Also, we are the first to report a mechanism by which CQ regulates the CSCs in TNBC through inhibition of the Janus-activated kinase 2 (Jak2)—signal transducer and activator of transcription 3 signaling pathway by reducing the expression of Jak2 and DNA methyltransferase 1. Stem Cells 2014;32:2309–2323